Atlas of Office Based Andrology Procedures - Mulhall, John P.; Jenkins, Lawrence C. (Springer International Publishing : Imprint: Springer, 2017)
This text provides a comprehensive resource and step-by-step guide to the office based procedures that would commonly occur in an andrology practice. The main purpose of the text is to serve as a "how-to" guide for urology providers and staff to help with initial training or as a refresher prior to performing the procedures. Written by experts in the field, each chapter begins with information on necessary equipment and shows a series of images (photos and illustrations) on key points during the procedure, including tips and tricks of the trade. Atlas of Office Based Andrology Procedures provides a valuable resource for urologists, nurse practitioners, and physician assistants in practice, residents and fellows in urological training, and nurses and medical assistants who help with these procedures.
Keywords: Medicine.; Nursing.; Urology.; elektronické knihy; electronic books